2021
DOI: 10.1152/jn.00546.2020
|View full text |Cite
|
Sign up to set email alerts
|

ATP-mediated increase in H+ flux from retinal Müller cells: a role for Na+/H+ exchange

Abstract: Small alterations in extracellular H+ can profoundly alter neurotransmitter release by neurons. We examined mechanisms by which extracellular ATP induces an extracellular H+ flux from Müller glial cells, which surround synaptic connections throughout the vertebrate retina. Müller glia were isolated from tiger salamander retinae and H+ fluxes examined using self-referencing H+-selective microelectrodes. Experiments were performed in 1 mM HEPES with no bicarbonate present. Replacement of extracellular sodium by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Recent work examining the molecular mechanisms underlying ATP-induced H + extrusion from retinal Müller glia suggests that the majority of acid is provided by Na + /H + exchange activity (Tchernookova et al, 2021). Consequently, we sought to determine if this was also the case for the ATP-induced extrusion of H + from brain astrocytes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work examining the molecular mechanisms underlying ATP-induced H + extrusion from retinal Müller glia suggests that the majority of acid is provided by Na + /H + exchange activity (Tchernookova et al, 2021). Consequently, we sought to determine if this was also the case for the ATP-induced extrusion of H + from brain astrocytes.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of dependence on extracellular sodium and the inability of Na + /H + inhibitors to reduce the flux differ from the ATP-induced alteration in H + flux previously detected in the radial glial cells (Müller cells) isolated from the retina of the tiger salamander. Upon removal of extracellular sodium, ATP-initiated H + fluxes from Müller cells were reduced by about 70%, and ATP-initiated H + fluxes were also inhibited by several pharmacological agents known to interfere with Na + /H + exchange (Tchernookova et al, 2021). These differences suggest that the molecular mechanism mediating the majority of H + flux in astrocytes cells is likely to be different from that in the retinal radial glial cells.…”
Section: Discussionmentioning
confidence: 96%
“…Additional experiments demonstrated that about 75% of the ATP-elicited increase in H + flux likely resulted from the extrusion of protons via Na + /H + exchange (Tchernookova et al, 2021). The complete removal of extracellular sodium and then with chelerythrine removed but ATP still present.…”
Section: H + Efflux From Glial Cells Elicited By Atpmentioning
confidence: 97%
“…The experiments described above were carried out in solutions in which the primary extracellular H + buffer was 1 mM HEPES, with no bicarbonate added. ATP-elicited increases in H + flux from Müller cells also persisted unchanged when solutions were bubbled for 15 min before use with 100% oxygen, to remove trace amounts of CO 2 from the atmosphere that could potentially be used by very high affinity bicarbonate transporters (Theparambil et al, 2014;Tchernookova et al, 2021).…”
Section: H + Efflux From Glial Cells Elicited By Atpmentioning
confidence: 98%
See 1 more Smart Citation